Upregulated HOXA9 expression is associated with lymph node metastasis in colorectal cancer - Watanabe, Yohei (Oncol Lett, 2018)
Homeobox A (HOXA) cluster genes, members of the HOX family, perform an important role in normal organ development. It has previously been reported that HOXA gene expression in various types of cancer is associated with poor patient outcomes. However, the role of HOXA genes, as well as their expression, in colorectal cancers (CRC) remains unknown. Therefore, the present study investigated HOXA gene expression in patients with CRC and revealed that HOXA9 expression was significantly increased in tumor tissues compared with non-tumor tissues. Additionally, the functional role of HOXA9 was assessed by knocking down the HOXA9 gene in CRC cells and by evaluating cell growth. Regarding gene expression, cases with positive HOXA9 expression (as detected by immunohistochemical staining) were significantly associated with higher TNM stage and positive lymph node metastasis, although no association was observed between increased HOXA9 levels and the rate of overall survival in the present cohort. Regarding the functional role, HOXA9 expression was demonstrated to be upregulated in patients with CRC and was associated with lymph node metastasis.